A High-Cholesterol Diet Increases Toll-like Receptors and Other Harmful Factors in the Rabbit Myocardium: The Beneficial Effect of Statins - Alkistis Kapelouzou; Michalis Katsimpoulas; Christos Kontogiannis; Irene Lidoriki; Georgios Georgiopoulos; Christos Kourek; Christos Papageorgiou; Konstantinos S. Mylonas; Spyridon Dritsas; Alexandros Charalabopoulos; Dennis V. Cokkinos (Current Issues in Molecular Biology, 2021)
Background: A high-cholesterol diet (HCD) induces vascular atherosclerosis through vascular inflammatory and immunological processes via TLRs. The aim of this study is to investigate the mRNA expression of TLRs and other noxious biomarkers expressing inflammation, fibrosis, apoptosis, and cardiac dysfunction in the rabbit myocardium during (a) high-cholesterol diet (HCD), (b) normal diet resumption and (c) fluvastatin or rosuvastatin treatment. Methods: Forty-eight male rabbits were randomly divided into eight groups (n = 6/group). In the first experiment, three groups were fed with HCD for 1, 2 and 3 months. In the second experiment, three groups were fed with HCD for 3 months, followed by normal chow for 1 month and administration of fluvastatin or rosuvastatin for 1 month. Control groups were fed with normal chow for 90 and 120 days. The whole myocardium was removed; total RNA was isolated from acquired samples, and polymerase chain reaction, reverse transcription PCR and quantitative real-time PCR were performed. Results: mRNA of TLRs 2, 3, 4 and 8; interleukin-6; TNF-a; metalloproteinase-2; tissue inhibitor of metalloproteinase-1; tumor protein 53; cysteinyl aspartate specific proteinase-3; and brain natriuretic peptide (BNP) increased in HCD. Statins but not resumption of a normal diet decreased levels of these biomarkers and increased levels of antifibrotic factors. Conclusions: HCD increases the levels of TLRs; inflammatory, fibrotic and apoptotic factors; and BNP in the rabbit myocardium. Atherogenic diets adversely affect the myocardium at a molecular level and are reversed by statins.